Temperature Reduction at Housing Scheme towards Sustainable Development - Sie Lee, Ong; mohamed, sulzakimin (Research in Management of Technology and Business, 2021)
Landscape design can support in temperature reduction for housing development and also can contribute to the beautification of surroundiong. It is a way in supporting the notion of sustainable development. Since the increase of temperature issues have been ubiquitously reflected to our environment; greenhouse Chlorofluorocarbon gasses (CFC) and urban heat effects, it is imperative to control or make improvement on our care of the planet. Therefore, instead of installing air-conditioning insides a house, landscape design is strongly recommended. It is a long-term cost effective and environmental approach to minimize the consumption of energy as well as reduce surrounding temperature simultaneously. This research is a study of tree planting as a landscape design at housing scheme as natural indoor temperature control. This is a way that offers benefits towards sustainable development..